3D printing technology of polymer-fiber composites in textile and fashion industry: A potential roadmap of concept to consumer. (15th September 2020) - Chakraborty, Samit; Biswas, Manik Chandra
Graphical abstract: Highlights: State-of-the-Art of 3DP technology in textile clothing industries. Materials and process descriptions relevant to manufacturing 3D printed polymer-fiber composites in textile and fashion. In depth discussion on SLS, SLA, FDM, inkjet, binder and micro-extrusion printing process. Future prospects of 3DP in regard to sustainability, novelty, complexity in fashion related fields. Personalized style and design-oriented textile apparel and accessories. Abstract: Three-dimensional printing (3DP) technology has gained an increased popularity in making prototypes in all types of manufacturing industries including automotive, healthcare, aerospace, sports, textile, apparel and fashion industry etc. Researchers, textile technologists, fashion designers, manufacturers and retailers have been working on adopting 3DP technology in their respective fields since the last decade. 3DP has been proved highly beneficial in reducing manufacturing time and production cost significantly regarding fiber reinforced composites fabrication. However, the application of this technology is still at niche while it comes to manufacturing everyday clothing. The purpose of this paper is to provide an integrative review of the existing literature to identify current state-of-the-art 3DP methods, materials, application in the textile and fashion industries. Further, the review considers the future of this technology with regard to sustainability, novelty, complexity in fashion related fields.